Immunohistochemical detection of metalloproteinase-9 (MMP-9), anti-oxidant like 1 protein (AOP-1) and synaptosomal-associated protein (SNAP-25) in the cerebella of dogs naturally infected with spontaneous canine distemper - Bregano, Livia Castanhas [UNESP]; Agostinho, Sabrina Donatoni [UNESP]; Rocatti, F. T. L. B. [UNESP]; Pires, Marcilia Cristina; Riva, Henrique Guimarães [UNESP]; Luvizotto, Maria Cecília Rui [UNESP]; Cardoso, Tereza Cristina [UNESP] (VM Media Group sp. z o.o, 2011)
In most viral infections of the central nervous system (CNS), the integrity of brain extracelluar matrix (ECM), oxidative stress and dysfunction in neuronal transmission may contribute to the observed pathology. The purpose of this study was to investigate the role of these factors in demyelinating canine distemper virus (CDV) infections. Regardless of ECM integrity, the expression of metalloproteinase-9 (MMP-9) was visualized in microglial-like cells, whereas the expression of anti-oxidant like-1 (AOP-1) and synaptosomal associated protein (SNAP-25) was frequently detected in Purkinje cells (r2 = 0.989; p < 0.05), regardless of whether the lesions were classified as acute or chronic. Increased numbers of immunolabeled microglia-like cells and reactive gliosis were observed in advanced cases of demyelinating CDV, suggesting that the expression of AOP-1 and SNAP-25 is correlated with the ultimate death of affected cells. Our findings bring a new perspective to understanding the role of the AOP-1, MMP-9 and SNAP-25 proteins in mediating chronic leukoencephalitis caused by CDV. (Folia Histochemica et Cytobiologica 2011; Vol. 49, No. 1, pp. 41–48)
Keywords: CDV; Antioxidative stress; Protein expression